Analysis of mRNA m6A modification and mRNA expression profiles in middle ear cholesteatoma - Xie, Shumin; Jin, Li; He, Jun; Fu, Jinfeng; Yin, Tuanfang; Ren, Jihao; Liu, Wei (Frontiers in Genetics, 2023)
Introduction: Middle ear cholesteatoma is characterized by hyperproliferation of keratinocytes. In recent decades, N6-methyladenosine (m6A) modification has been shown to play an essential role in the pathogenesis of many proliferative diseases. However, neither the m6A modification profile nor its potential role in the pathogenesis of middle ear cholesteatoma has been investigated to date. Therefore, this study aimed to explore m6A modification patterns in middle ear cholesteatoma.Materials and Methods: An m6A mRNA epitranscriptomic microarray analysis was performed to analyze m6A modification patterns in middle ear cholesteatoma tissue (n=5) and normal post-auricular skin samples (n=5). Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses were performed to predict the potential biological functions and signaling pathways underlying pathogenesis of middle ear cholesteatoma. Subsequently, m6A modification levels were verified by methylated RNA immunoprecipitation-qPCR (MeRIP-qPCR) in middle ear cholesteatoma tissues and normal skin samples, respectively.Results: A total of 6865 distinctive m6A-modificated mRNAs were identified, including 4620 hypermethylated and 2245 hypomethylated mRNAs, as well as 9162 differentially expressed mRNAs, including 4891 upregulated and 4271 downregulated mRNAs, in the middle ear cholesteatoma group relative to the normal skin group. An association analysis between methylation and gene expression demonstrated that expressions of 1926 hypermethylated mRNAs were upregulated, while 2187 hypomethylated mRNAs and 38 hypermethylated mRNAs were downregulated. Moreover, GO analysis suggested that differentially methylated mRNAs might influence cellular processes and biological behaviors, such as cell differentiation, biosynthetic processes, regulation of molecular functions, and keratinization. KEGG pathway analysis demonstrated that the hypermethylated transcripts were involved in 26 pathways, including the Hippo signaling pathway, the p53 signaling pathway, and inflammatory mediator regulation of transient receptor potential (TRP) channels, while the hypomethylated transcripts were involved in 13 pathways, including bacterial invasion of epithelial cells, steroid biosynthesis, and the Hippo signaling pathway.Our study presents m6A modification patterns in middle ear cholesteatoma, which may exert regulatory roles in middle ear cholesteatoma. The present study provides direction for mRNA m6A modification-based research on the epigenetic etiology and pathogenesis of middle ear cholesteatoma.